Expansion Microscopy for Cell Biology Analysis in Fungi - Götz, Ralph; Panzer, Sabine; Trinks, Nora; Eilts, Janna; Wagener, Johannes; Turrà, David; Di Pietro, Antonio; Sauer, Markus; Terpitz, Ulrich (Frontiers in Microbiology, 2020)
Super-resolution microscopy has evolved as a powerful method for subdiffraction-resolution fluorescence imaging of cells and cellular organelles, but requires sophisticated and expensive installations. Expansion microscopy (ExM), which is based on the physical expansion of the cellular structure of interest, provides a cheap alternative to bypass the diffraction limit and enable super-resolution imaging on a conventional fluorescence microscope. While ExM has shown impressive results for the magnified visualization of proteins and RNAs in cells and tissues, it has not yet been applied in fungi, mainly due to their complex cell wall. Here we developed a method that enables reliable isotropic expansion of ascomycetes and basidiomycetes upon treatment with cell wall degrading enzymes. Confocal laser scanning microscopy (CLSM) and structured illumination microscopy (SIM) images of 4.5-fold expanded sporidia of Ustilago maydis expressing fluorescent fungal rhodopsins and hyphae of Fusarium oxysporum or Aspergillus fumigatus expressing either histone H1-mCherry together with Lifeact-sGFP or mRFP targeted to mitochondria, revealed details of subcellular structures with an estimated spatial resolution of around 30 nm. ExM is thus well suited for cell biology studies in fungi on conventional fluorescence microscopes.